(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This review evaluates by-product protein sources used in animal feed, focusing on their nutritional composition, digestibility, processing methods, safety concerns, and applications across livestock and aquaculture species. By analyzing studies on amino acid profiles and protein quality, it highlights the capacity of both animal-derived and plant-based by-products to meet essential amino acid requirements. The review synthesizes evidence on digestibility metrics influenced by processing techniques such as enzymatic hydrolysis and fermentation, demonstrating improvements in nutrient bioavailability. Additionally, processing methods are explored for their efficacy in reducing contaminants including pathogens, antibiotics, and heavy metals, thereby enhancing feed safety. Safety challenges associated with chemical residues and antimicrobial resistance are addressed alongside mitigation strategies. Finally, comparative analyses underscore the impacts of these proteins on animal performance, growth, immune responses, and sustainability metrics. This integrated assessment provides valuable insights for optimizing the use of by-product proteins in sustainable animal nutrition and identifies areas warranting further investigation.